Socialization Of Stress Management And Motivation For Forki Riau Karate Athletes In Preparation For The National Championship - Salsabilah Salsabilah; Aidil Syaputra; Agung Hilmi; Wahdi Arfa Adha; Purwanto Purwanto; Rahmad Diyanto (CV. AFDIFAL MAJU BERKAH, 2025)
The success of athletes in competitions is not solely determined by technical skills and physical condition, but also by mental readiness. Athletes who experience high levels of stress tend to lose focus, suffer from excessive anxiety, and experience a decline in motivation, all of which negatively impact their performance. In the context of FORKI Riau karate athletes, psychological aspects are often overlooked in the preparation for national championships. Therefore, this community service program aims to assist athletes in managing stress and enhancing motivation through a sports psychology approach. The program will be carried out over six months, starting with an initial survey to measure the athletes' stress and motivation levels, as well as interviews with coaches to identify stress-triggering factors. Stress management training will then be provided using relaxation techniques, breathing exercises, mindfulness, and positive self-talk. To boost motivation, athletes will also be equipped with goal-setting strategies, confidence-building techniques, and both intrinsic and extrinsic motivational methods. The program involves active participation from athletes, coaches, and a service team consisting of one leader and six members, each with specific roles. Evaluation will be conducted through follow-up surveys and interviews to assess the impact of the training on the athletes’ mental preparedness. It is expected that this program will help athletes compete with greater confidence and focus, while also offering valuable insights for coaches on the application of sports psychology to improve athletic performance. Furthermore, the program may serve as an academic reference for further research in the fields of stress management and athlete motivation. By combining scientific methods with practical implementation, this initiative is expected to contribute to the improved performance of FORKI Riau athletes at the national level